2008
DOI: 10.1088/0022-3727/41/12/125408
|View full text |Cite
|
Sign up to set email alerts
|

High piezoelectric properties and domain configuration in BaTiO3ceramics obtained through the solid-state reaction route

Abstract: BaTiO3 ceramics with a high piezoelectric coefficient have been successfully obtained through the conventional solid-state reaction route starting from ordinary BaCO3 and TiO2 powders. The ceramics sintered at 1210 °C exhibit excellent piezoelectric properties of d33 = 419 pC N−1 and kp = 0.453 with tan δ = 1.36% at room temperature. The crystallographic structure, the microstructure and the domain pattern were investigated. It has been revealed that d33 increases and the average domain width in the poled BaTi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(75 citation statements)
references
References 25 publications
6
69
0
Order By: Relevance
“…Since there is no apparent difference in crystal structure and relative density, the grain size should be a main factor such that the piezoelectric constant increases apparently with increasing grain size. However, a study by Shao et al [18] indicated that for the conventional sintered BaTiO 3 ceramics with larger grain size, the piezoelectric constant decreases from 419 pC/N to 185 pC/N when the average grain size increases from 7 μm to 19 μm. Hence, there could be a critical grain size with which the piezoelectric constant of BST has a maximum value.…”
Section: Piezoelectric Coefficientmentioning
confidence: 99%
“…Since there is no apparent difference in crystal structure and relative density, the grain size should be a main factor such that the piezoelectric constant increases apparently with increasing grain size. However, a study by Shao et al [18] indicated that for the conventional sintered BaTiO 3 ceramics with larger grain size, the piezoelectric constant decreases from 419 pC/N to 185 pC/N when the average grain size increases from 7 μm to 19 μm. Hence, there could be a critical grain size with which the piezoelectric constant of BST has a maximum value.…”
Section: Piezoelectric Coefficientmentioning
confidence: 99%
“…13) On the other hand, Shao et al recently reported that average grain size, rather than domain width, significantly influences the piezoelectric properties in normally sintered BaTiO 3 ceramics. 14) They revealed that the piezoelectric constant d 33 values decrease from 419 pC/N to 185 pC/N when its average grain size increases from 3.5 to 9.5¯m, while its average domain width remains approximately constant at around 0.24¯m. Apparently, there are still controversy existing about which one is a crucial factor to influence the piezoelectric properties between grain size and nano-domain structure.…”
Section: Introductionmentioning
confidence: 99%
“…As far as BT is concerned, astonishingly high d 33 values of 350-460 pC/N have been reported in ceramics prepared by microwave sintering, ordinary sintering, and two-step sintering processes. [15][16][17] Additionally, BT does not possess any volatile elements and its properties can be easily tailored by site engineering. The solid solution of BT and barium zirconate (BaZrO 3 ), Ba(Zr y Ti 1Ày )O 3 (BZT) was considered as an important material for the fabrication of ceramic capacitors because Zr 4þ is chemically more stable than Ti 4þ .…”
mentioning
confidence: 99%